Comparative analysis of waste-to-energy alternatives for a low-capacity power plant in Brazil - Ferreira, Elzimar Tadeu de F. [UNESP]; Balestieri, Jose Antonio P. [UNESP] (Sage Publications Ltd, 2018)
The Brazilian National Solid Waste Policy has been implemented with some difficulty, especially in convincing the different actors of society about the importance of conscious awareness among every citizen and businesses concerning adequate solid waste disposal and recycling. Technologies for recovering energy from municipal solid waste were considered in National Solid Waste Policy (NSWP), given that their technical and environmental viability is ensured, being the landfill biogas burning in internal combustion engines and solid waste incineration suggested options. In the present work, an analysis of current technologies and a collection of basic data on electricity generation using biogas from waste/liquid effluents is presented, as well as an assessment of the installation of a facility that harnesses biogas from waste or liquid effluents for producing electricity. Two combined cycle concepts were evaluated with capacity in the range 4-11MW, gas turbine burning landfill biogas and an incinerator that burns solid waste hybrid cycle, and a solid waste gasification system to burn syngas in gas turbines. A comparative analysis of them demonstrated that the cycle with gasification from solid waste has proved to be technically more appealing than the hybrid cycle integrated with incineration because of its greater efficiency and considering the initially defined guidelines for electricity generation. The economic analysis does not reveal significant attractive values; however, this is not a significant penalty to the project given the fact that this is a pilot low-capacity facility, which is intended to be constructed to demonstrate appropriate technologies of energy recovery from solid waste.
Keywords: Municipal solid waste; waste-to-energy technologies; combined cycle; gasification; incineration